THE COMMITMENT OF HEALTH ACADEMY LECTURER AS A WORKING MOTHER IN BREASTFEEDING EXCLUSIVELY ON HER BABY - Tri Utami, Woro; Rahmawati, Rahmawati (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2017)
Higher Education Lecturers certainly have a high level of education and a good understanding of exclusive breastfeeding. However the duties, principals and functions of lecturers are very much and time consuming to make the risk of failure of the lecturer as a mother working in giving exclusive breastfeeding to her baby.The design used in this research is descriptive survey. The subjects in this study were lecturers of the Rajekwesi Health Academy who had 6-24 months of infant, with the object of exclusive breastfeeding research and factors related to exclusive breastfeeding and using descriptive analysis of cross tab results.Description of knowledge, attitude, and job is found that almost all respondents have good knowledge (80%) all respondents have a positive attitude (100%), and all respondents working mother (100%) and all respondents do not give Exclusive breast milk (100%). Which is weak between knowledge and exclusive breastfeeding. There is a weak relationship between attitude and exclusive breastfeeding. There is a close relationship between work and exclusive breastfeeding. The Occupational Factor is the most dominant factor of its relationship in the failure of Exclusive Breastfeeding at Akes Rajekwesi Bojonegoro.The Institution expected to make regulation which facilitate the success of exclusive breastfeeding of its employees. To the respondents expected to further reinforce the commitment to provide exclusive breastfeeding for her baby. The results of this study are expected to be used as a reference for conducting research development on Exclusive Breast Milk.